Anomalous aortic origin of coronary arteries: Early results on clinical management from an international multicenter study. (15th September 2019) - Padalino, Massimo A.; Franchetti, Nicola; Sarris, George E.; Hazekamp, Mark; Carrel, Thierry; Frigiola, Alessandro; Horer, Jurgen; Roussin, Regine; Cleuziou, Julie; Meyns, Bart; Fragata, Jose; Telles, Helena; et al.
Abstract: Background: Anomalous aortic origin of coronary arteries (AAOCA) is a rare abnormality, whose optimal management is still undefined. We describe early outcomes in patients treated with different management strategies. Methods: This is a retrospective clinical multicenter study including patients with AAOCA, undergoing or not surgical treatment. Patients with isolated high coronary take off and associated major congenital heart disease were excluded. Preoperative, intraoperative, anatomical and postoperative data were retrieved from a common database. Results: Among 217 patients, 156 underwent Surgical repair (median age 39 years, IQR: 15–53), while 61 were Medical (median age 15 years, IQR: 8–52), in whom AAOCA was incidentally diagnosed during screening or clinical evaluations. Surgical patients were more often symptomatic when compared to medical ones (87.2% vs 44.3%, p < 0.001). Coronary unroofing was the most frequent procedure (56.4%). Operative mortality was 1.3% (2 patients with preoperative severe heart failure). At a median follow up of 18 months (range 0.1–23 years), 89.9% of survivors are in NYHA ≤ II, while only 3 elderly surgical patients died late. Return to sport activity was significantly higher in Surgical patients (48.1% vs 18.2%, p < 0.001). Conclusions: Surgery for AAOCA is safe and with low morbidity. When compared to Medical patients, who remain on exercise restriction and medical therapy, surgical patients have a benefit in terms of symptoms and return to normal life. Since the long term-risk of sudden cardiac death is still unknown, we currently recommend accurate long term surveillance in all patients with AAOCA. Highlights: Anomalous aortic origin of coronary arteries (AAOCA) is a rare abnormality and its optimal management is still undefined. In this large clinical multicenter study on AAOCA, we demonstrate that surgical repair is safe and with low morbidity. Compared to medical treatment, surgery for AAOCA provides an important benefit in terms of returning to normal lifestyle. Since the uncertain long term-risk, a regular long term surveillance is recommended in all patients with AAOCA.